Compliance of Anesthesia Personnel Towards Regional Anesthesia Checklist - Zia, Aneeqa; Hashmi, Faiqa; Khan, Safdar Ali (Biological and Clinical Sciences Research Journal, 2025)
Ensuring adherence to institutional protocols is crucial for minimising complications and enhancing patient safety during regional anaesthesia. Standardised checklists are endorsed globally to improve procedural compliance and promote uniformity in anaesthesia practice. Objective: To assess the compliance of anaesthetists with institutional standard practice protocols for regional anaesthesia at a tertiary care hospital. Methods: A cross-sectional study was conducted in the Anaesthesia Department of National Hospital and Medical Centre, Lahore, from August 2024 to February 2025. A total of 83 anaesthetists were enrolled, including both consultants and postgraduate residents. A standardized pre-procedure checklist comprising 9 items was used to evaluate compliance, based on guidelines provided by the American Society of Regional Anesthesia (ASRA) and the WHO pre-block checklist. Data were analysed using SPSS version 25. Descriptive statistics were computed, and the chi-square test was applied to determine associations between compliance and variables such as designation and type of surgical procedure. A p-value <0.05 was considered statistically significant. Results: Overall compliance with regional anaesthesia protocols was 86%. The highest compliance rates were observed for equipment readiness (97.59%), drug labelling (95.18%), and obtaining surgical consent (93.98%). Compliance during the "time-out" phase was slightly lower at 92.77%. Consultants demonstrated a marginally higher compliance rate (88.5%) compared to postgraduate residents (84.2%). No statistically significant differences in compliance were observed based on anaesthetist designation or type of surgical procedure (p>0.05). Conclusion: High compliance with regional anaesthesia protocols was observed, particularly in equipment preparation, drug labelling, and consent verification. While consultants showed marginally better adherence than residents, overall compliance remained commendable across all practitioner levels. Continued emphasis on checklist implementation and periodic audits can further reinforce adherence to protocol.